Empirical evidence of risk-shifting behavior in the commercial airline industry - Oberson de Souza, Pierre (2021)
In this study, we empirically evaluate the occurrence of risk-shifting (asset substitution) behavior. We conducted the study using a diff-in-diff approach with several specifications in a natural experiment environment due to two simultaneous exogenous shocks (increase in fuel price and decrease in air travel) that affected the American commercial airline industry. The results, in line with risk-shifting theory, are robust without indications that they are driven by reverse causality. Airlines that were closer to financial distress before the shock increase their risky investments during the shock when compared to other airlines. Empirical studies that aim to evaluate the presence of risk-shifting have mixed results. This study contributes to the literature by providing a new approach, with a unique dataset, that resulted in findings in favor to risk-shifting predictions.